Neocoprozercon europaeus gen. nov., sp. nov., the first member of the family Coprozerconidae (Acari: Mesostigmata) in the Palaearctic Region - Fenďa, Peter; Mašán, Peter (Zootaxa, 2012)
A new genus and species, Neocoprozercon europaeus gen. nov., sp. nov., are described, based on adults and deutonymphscollected from soil detritus and animal excrement in a cave in theČierna hora Mts., Western Carpathians, Slovakia.Amendments to the diagnosis of the family Coprozerconidae Moraza & Lindquist, 1998 and a key to the genera are presented.